A Pilot Study of Blog Use for Internal Knowledge Sharing in Academic Libraries - Forcier, Eric (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
While Library 2.0 has brought attention to the value of social media for service delivery, the use of such tools for internal knowledge sharing remains largely unexplored. Through semi-structured interviews with five librarians, this pilot study examines the current use of blogs by academic librarians for internal communication. Alors que la bibliothèque 2.0 a attiré l’attention sur la valeur des médias sociaux pour la prestation de service, l’utilisation de ces outils aux fins de partage des connaissances à l’interne demeure largement inexplorée. Au moyen d’entrevues semi structurées avec cinq bibliothécaires, cette étude pilote porte sur l’utilisation actuelle des blogues par les bibliothécaires universitaires aux fins de communication interne.